Pengembangan Skala Pengukuran Rasa Percaya Diri Siswa Kombi: Instrumen Pendukung Permainan Antaboga - Nur Azizah, Fitria Ayu; Setyawati, Sri Panca; Khususiyah, Khususiyah; Setyaputri, Nora Yuniar (Universitas Nusantara PGRI Kediri, 2023)
Having good self-confidence plays an important role in today's modern era, especially when going straight into society because individual who does not have good self-confidence will always feel anxious, insecure and not feel free to do whatever he wants in life. The purpose of this study was to make a measuring instrument for students' self-confidence as an instrument to support the Antaboga game by using the method of non-test instruments. Based on the results of the validity and reliability tests conducted by 2 material experts, the overall value of content validity was 0.8, then continued with the test of 2 BK teacher users, the overall value of content validity was 0.7, as well as the user test conducted by 30 students of class XI SMAN 2 Kota Kediri, obtained 23 valid items with a reliable coefficient of 0.875. Of the 23 items that were declared valid, they could represent each indicator of self-confidence. Based on the validity and reliability tests conducted, it can be concluded that this scale for measuring student self-confidence can be used as a tool to measure high school student self-confidence at the next research stage.